PERAN PENYULUH PERIKANAN TERHADAP KELOMPOK PEMBUDIDAYA IKAN PATIN (Pangasius sp) DI DESA PENYINGGAHAN ULU KECAMATAN PENYINGGAHAN KABUPATEN KUTAI BARAT - Niki Ristanto; Elly Purnamasari; Muhammad Syafril (2339-1324, 2022)
The purpose of this research is to find out the role of fishery extension workers in developing tilapia breeding group (Oreochromis niloticus) in The Village of Ulu Regency, West Kutai Regency. Catfish (Pangasius sp) This research was conducted in The Village of Penyinggahan Ulu District, West Kutai Regency. Sampling method used is proportional random sampling method with the number of respondents 35 members of the group of farmers Catfish ( Pangasius sp) Data collection techniques with interviews using questionnaires then in the analysis using interval class formula and likert scale with three categories namely, high, medium, low. Research indicators are the role of extension workers who refer to, the role of extension workers as motivators with an average score of 13.97 is in the high category, educators with an average score of 10.23 are in the high category, catalysts with an average score of 7.00 are in the medium category, organizers with an average score of 8.80 are in the high category, communicators with an average score of 7.71 are in the high category, and advisors with an average score of 8.46 are in the high category. The results obtained from this study are the role of fishery extension workers in developing the Patin Fish breeding group (Pangasius sp) fall into the high category with an average score of 56.17. Keyword : Role of Fisheries Extension, Patin Fish Cultivator Group (Pangasius sp).